Between Successful and Unsuccessful Ageing: Selected Aspects and Contexts - Andrzej Klimczuk; Łukasz Tomczyk (Pedagogical University of Krakow, 2019)
We provide to readers the 11th volume of the "Czech-Polish-Slovak Studies in Andragogy and Social Gerontology" series. We are delighted to announce that the presented study is the result of the work of scientists from seven countries: Austria, China, Ghana, Hungary, Japan, Poland, and Russia. This international collection of texts is part of the global discourse on the determinants of adult education and the functioning of people in late adulthood. The 11th volume is a collection of research results that show both the positive and negative dimensions of ageing through the prism of research experience from various geographical and cultural areas. The researchers invited to the presented volume tried to illustrate the issues assigned to the following topics: ageing with dignity; retirement age; assumptions and conditions resulting from living in the home; the relationship between challenges concerning life expectancy and needs; care and ageing services; and foundations and potential changes in pension systems. The research results presented in this volume have a common denominator, which is caring for the quality of life of the older people regardless of their place of residence. Thus, the study "Between Successful and Unsuccessful Ageing: Selected Aspects and Contexts" brings new insights from scientists who scrupulously characterize the complexity of processes that affect the positive and negative conditions of functioning in old age, which is a mosaic of various nuances. Inviting readers to familiarize themselves with the content of the monograph, we would like to thank the reviewers who contributed to the improvement of the quality of the texts and open new fields for participation in further joint publishing projects.
Keywords: J14; J18; 330; Age-friendly Housing; Central and Eastern Europe; Seniors' Needs; Socialism; Housing Stock; Successful Ageing; Social Gerontology; Activity Theory; Disengagement Theory; Critical Gerontology; Welfare State; Pensions; Compensation Payments; Life-Sustaining Needs; Care; Protection; Age Discrimination; Elderly Care Policy; Population Ageing; Policy Evolution; Social Security; Elderly Care Service; Modern Pension Systems; Pay-as-you-go; Pension Reform; Retirement